APPORT D’UNE EGLISE AU DEVELOPPEMENT DE SON MILIEU D’IMPLANTATION : CAS DU BUREAU DIOCESAIN DE DEVELOPPEMENT DU DIOCESE D’ISIRO-NIANGARA DE 2010 A 2014 - Oseyatoko, Marcel; AZANGA, Lucien DUOMBE; N’GBALE, Jacques – Richard FATAKI (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The non-profit-making associations constitute significant actresses as regards development in the countries of the south. ¶This research falls under this logic.¶ ¶The Office Diocesan for the Development of the diocese of Isiro-Niangara continues a certain number of objectives relating to the needs for its operating range. ¶Thus this essay wants to show if starting from the strategies implemented by this organization, the objectives assigned to him were achieved initially; ¶measured the contribution of each partner to the financing of the activities then; ¶to finally appreciate the output of these last after execution of the program.¶ ¶It is obvious to note that the aims in view by the Office Diocesan of Development ¶/ ISIRO are achieved but with a weak cover in its medium of establishment. ¶If the profit communities capitalize these assets, it is necessary to hope on takeoff.¶